Single-dose mRNA Vaccine Effectiveness Against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), Including Alpha and Gamma Variants: A Test-negative Design in Adults 70 Years and Older in British Columbia, Canada. (9th July 2021) - Skowronski, Danuta M; Setayeshgar, Solmaz; Zou, Macy; Prystajecky, Natalie; Tyson, John R; Galanis, Eleni; Naus, Monika; Patrick, David M; Sbihi, Hind; El Adam, Shiraz; Henry, Bonnie; Hoang, Linda M N; et al.
Abstract: Background: Randomized-controlled trials of messenger RNA (mRNA) vaccine protection against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) included relatively few elderly participants. We assess single-dose mRNA vaccine effectiveness (VE) in adults ≥ 70 years old in British Columbia, Canada, where second doses were deferred by up to 16 weeks and where a spring 2021 wave uniquely included codominant circulation of Alpha (B.1.1.7) and Gamma (P.1) variants of concern (VOC). Methods: Analyses included community-dwelling adults ≥ 70 years old with specimen collection between 4 April (epidemiological week 14) and 1 May (week 17) 2021. Adjusted VE was estimated by test-negative design. Cases were reverse-transcription polymerase chain reaction (RT-PCR) test-positive for SARS-CoV-2, and controls were test-negative. Vaccine status was defined by receipt of a single-dose ≥ 21 days before specimen collection, but a range of intervals was assessed. Variant-specific VE was estimated against viruses genetically characterized as Alpha, Gamma or non-VOC lineages. Results: VE analyses included 16 993 specimens: 1226 (7%) test-positive cases and 15 767 test-negative controls. Of 1131 (92%) genetically characterized viruses, 509 (45%), 314 (28%), and 276 (24%) were Alpha, Gamma, and non-VOC lineages, respectively. At 0–13 days postvaccination, VE was negligible at 14% (95% confidence interval [CI], 0–26) but increased from 43% (95% CI, 30–53) at 14–20 days to 75% (95% CI, 63–83) at 35–41 days postvaccination. VE at ≥ 21 days postvaccination was 65% (95% CI, 58–71) overall: 72% (95% CI, 58–81), 67% (95% CI, 57–75), and 61% (95% CI, 45–72) for non-VOC, Alpha, and Gamma variants, respectively. Conclusions: A single dose of mRNA vaccine reduced the risk of SARS-CoV-2 by about two-thirds in adults ≥ 70 years old, with protection only minimally reduced against Alpha and Gamma variants. Abstract : Vaccine effectiveness estimated by test-negative design in British Columbia, Canada, shows one dose of mRNA vaccine reduced the risk of SARS-CoV-2 infection in adults ≥70-years-old by about two-thirds, with protection only minimally reduced against Alpha (B.1.1.7) and Gamma (P.1) variants.